Dynamic full-field optical coherence tomography for live-cell imaging and growth-phase monitoring in Aspergillus fumigatus - Maldiney, Thomas; Garcia-Hermoso, Dea; Sitterlé, Emilie; Chassot, Jean-Marie; Thouvenin, Olivier; Boccara, Claude; Blot, Mathieu; Piroth, Lionel; Quenot, Jean-Pierre; Charles, Pierre-Emmanuel; Aimanianda, Vishukumar; Podac, Bianca; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The diagnosis of cutaneous manifestations of deep mycoses relies on both histopathological and direct examination. Yet, the actual diagnostic criteria cannot prevent missed cases including invasive aspergillosis that would require the development of novel diagnosis approach and imaging tools. We recently introduced the use of dynamic full-field optical coherence tomography (D-FF-OCT) in fungal diagnostics with a definition approaching conventional microscopy and the ability to return metabolic information regarding different fungal species. The present work focuses on subcellular dynamics and live-cell imaging of Aspergillus fumigatus with D-FF-OCT to follow the fungal growth stages. Methods Aspergillus fumigatus ATCC 204305 quality-control strain was used for all imaging experiments following incubation times varying between 24-72h at 30°C in a humidified chamber on Sabouraud Dextrose Agar. Fungal growth was subsequently monitored with D-FF-OCT for up to 5h at room temperature. Results D-FF-OCT images allow not only the visualization of intracellular trafficking of vacuoles, but also an evolving dynamic segmentation of conidiophores depending on chronological development and aging of the hyphae. The same apply to conidial heads with a most intense D-OCT signal coming from vesicles uncovering a changing dynamic within a few hours only as well as complete extinction following subsequent drying of the Sabouraud Dextrose Agar. Discussion These results bring additional data towards the ability of D-FF-OCT to monitor some of the main life-cycle processes, dynamics as well as intracellular trafficking of vacuoles in Aspergillus fumigatus. Such complementary metabolic information might help both clinician and microbiologist for the diagnosis of superficial fungal infections.